Political propaganda in Mexico and the United States: discordant theoretical - methodological approaches (2019)
The most used mass communication vehicle between parties or candidates during current electoral processes is the television political propaganda. However, in academic terms, there is no master theoretical framework that can contribute to the disciplinary consolidation of the topic under discussion. In this paper, a systematic review of research trends is carried out. As a result of an exploratory design, the papers regarding the subject were identified, ordered and studied. The theoretical - methodological postulates of a group of Mexican and North American authors, who have analyzed the contents and effects of the political spot, are shown here. The main finding is that there is no disciplinary consolidation in Mexico because the authors make intermittent approaches to the subject. In addition, qualitative methodologies dominate the researches that are undertaken, and usage of statistics has been marginal in quantitative ones. In contrast, in the United States there is a sophistication in the statistical models used, various theoretical assumptions have been tested, and those could make up an element that shapes the incipient analysis of political communication in Mexico and Latin America. It is concluded that the tension between qualitative and quantitative research is regional in nature: In Mexico, the pragmatism of the social sciences dominates the field; In contrast, there is a structured field in the United States.